Re-growth of single-walled carbon nanotube by hot-wall and cold-wall chemical vapor deposition. (December 2015) - Wang, Huafeng; Yamada, Chisato; Liu, Jia; Liu, Bilu; Tu, Xiaomin; Zheng, Ming; Zhou, Chongwu; Homma, Yoshikazu
Abstract: Single-walled carbon nanotube (SWCNT) was synthesized from short nanotubes using chemical vapor deposition (CVD) and the associated factors affecting the re-growth of the SWCNT were both investigated and optimized. Long, dense nanotubes were prepared from a mixture of acetylene and ethanol on air-annealed ST-cut quartz substrates by hot-wall CVD. Raman and photoluminescence analyses of the resulting material demonstrated that SWCNT was generated from the initial seeds since the chiralities of the seeds were maintained in the re-grown SWCNT. The re-growth of SWCNT was also achieved by cold-wall CVD. In both CVD systems, the efficiency of SWCNT re-growth was largely determined by the pretreatment conditions and growth parameters. By varying these factors, the growth of SWCNT from seeds was controlled. The re-growth mechanism is discussed based on experimental observations.